A Convexity Theorems for Boundaries of Ordered Symmetric Spaces - Hilgert, Joachim (Canad. J. Math.)

Leptin, H. und J. Ludwig. Unitary Representation Theory of Exponential Lie Groups (De Gruyter, Berlin, 1994) - Hilgert, Joachim (Zentralblatt für Math.)

Detecting the symmetry of attractors - Barany, Ernest; Dellnitz, Michael; Golubitsky, Martin (Physica D: Nonlinear Phenomena)

Normal forms for linear Hamiltonian vector fields commuting with the action of a compact Lie group - Melbourne, Ian; Dellnitz, Michael (Mathematical Proceedings of the Cambridge Philosophical Society)
Abstract We obtain normal forms for infinitesimally symplectic matrices (or linear Hamiltonian vector fields) that commute with the symplectic action of a compact Lie group of symmetries. In doing so we extend Williamson's theorem on normal forms when there is no symmetry present. Using standard representation-theoretic results the symmetry can be factored out and we reduce to finding normal forms over a real division ring. There are three real division rings consisting of the real, complex and quaternionic numbers. Of these, only the real case is covered in Williamson's original work.

The structure of symmetric attractors - Melbourne, Ian; Dellnitz, Michael; Golubitsky, Martin (Archive for Rational Mechanics and Analysis)

The equivariant Darboux theorem - Dellnitz, Michael (Lectures in Applied Mathematics)

A note on property (T) of orthogonal polynomials - Lasser, R.; Rösler, Margit (Archiv der Mathematik)
Keywords: General Mathematics

Lie Semigroups and their Applications

Corwin, L. und F.P. Greenleaf. Representations of Nilpotent Lie Groups and their Applications. (Cambridge University Press, 1990) - Hilgert, Joachim (JBer. DMV)

Mechanisms of Symmetry Creation - Dellnitz, Michael; Golubitsky, Martin; Melbourne, Ian (Bifurcation and Symmetry)